2021
DOI: 10.1136/gpsych-2021-100564
|View full text |Cite
|
Sign up to set email alerts
|

Urban–rural disparities in mild cognitive impairment and its functional subtypes among community-dwelling older residents in central China

Abstract: BackgroundSubstantial variations in the prevalence of mild cognitive impairment (MCI) and its subtypes have been reported, although mostly in geographically defined developed countries and regions. Less is known about MCI and its subtypes in rural areas of less developed central China.AimsThe study aimed to compare the prevalence of MCI and its subtypes in residents aged 65 years or older in urban and rural areas of Hubei Province, China.MethodsParticipants aged 65 years or older were recruited between 2018 an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 17 publications
(8 citation statements)
references
References 33 publications
(37 reference statements)
0
8
0
Order By: Relevance
“…In urban areas, older adults have a relatively high level of education, healthy lifestyles (less smoking and drinking and more physical activities) and better health conditions (lower ratio of hypertension and diabetes). 37 However, significant urban-rural differences remained between the serum lipid parameters and cognitive impairment in the adjusted model 2. This suggests that rural-dwelling older adults should be considered a priority for the prevention of cognitive impairment.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…In urban areas, older adults have a relatively high level of education, healthy lifestyles (less smoking and drinking and more physical activities) and better health conditions (lower ratio of hypertension and diabetes). 37 However, significant urban-rural differences remained between the serum lipid parameters and cognitive impairment in the adjusted model 2. This suggests that rural-dwelling older adults should be considered a priority for the prevention of cognitive impairment.…”
Section: Discussionmentioning
confidence: 95%
“…One possible reason for these differences in lipids and cognitive impairment is that in rural areas, older adults have a lower education level and there is a higher rate of hypertension. In urban areas, older adults have a relatively high level of education, healthy lifestyles (less smoking and drinking and more physical activities) and better health conditions (lower ratio of hypertension and diabetes) 37. However, significant urban-rural differences remained between the serum lipid parameters and cognitive impairment in the adjusted model 2.…”
Section: Discussionmentioning
confidence: 98%
“…44 In addition to vascular complication, a study comparing the prevalence of MCI in people aged 65 or older in urban and rural areas of China, reported that the prevalence of MCI in rural areas of China is twice that of urban areas, suggesting a pressing need to improve AD management in rural China. 45 The overlap of stroke and early AD in China complicates clinical diagnosis, especially given the large population. For example, a 75year-old retired engineer first presented in 2014 with memory loss, reporting that he had forgotten the names of people he had known for years.…”
Section: Difficulties Due To a Large Population And Comorbidities In ...mentioning
confidence: 99%
“…Hypoperfusion may also exacerbate tau pathology through the upregulation of tau‐phosphorylating enzymes and indirectly via the amyloid cascade 44 . In addition to vascular complication, a study comparing the prevalence of MCI in people aged 65 or older in urban and rural areas of China, reported that the prevalence of MCI in rural areas of China is twice that of urban areas, suggesting a pressing need to improve AD management in rural China 45 …”
Section: Difficulties Due To a Large Population And Comorbidities In ...mentioning
confidence: 99%
“…Mild cognitive impairment (MCI) is a transitional state between normal ageing and early dementia. The prevalence of MCI in older adults aged 60 years or above in China ranges from 15.5% to 27.8%, and the proportion of MCI progressing to AD within 5 years is 10%–15% every year 5 6…”
Section: Introductionmentioning
confidence: 99%